Fission yeast strains with circular chromosomes require the 9-1-1 checkpoint complex for the viability in response to the anti-cancer drug 5-fluorodeoxyuridine. - Hossain Mohammad Shamim; Yukako Minami; Daiki Tanaka; Shinobu Ukimori; Johanne M Murray; Masaru Ueno (PLoS ONE, 2017)
Thymidine kinase converts 5-fluorodeoxyuridine to 5-fluorodeoxyuridine monophosphate, which causes disruption of deoxynucleotide triphosphate ratios. The fission yeast Schizosaccharomyces pombe does not express endogenous thymidine kinase but 5-fluorodeoxyuridine inhibits growth when exogenous thymidine kinase is expressed. Unexpectedly, we found that 5-fluorodeoxyuridine causes S phase arrest even without thymidine kinase expression. DNA damage checkpoint proteins such as the 9-1-1 complex were required for viability in the presence of 5-fluorodeoxyuridine. We also found that strains with circular chromosomes, due to loss of pot1+, which have higher levels of replication stress, were more sensitive to loss of the 9-1-1 complex in the presence of 5-fluorodeoxyuridine. Thus, our results suggest that strains carrying circular chromosomes exhibit a greater dependence on DNA damage checkpoints to ensure viability in the presence of 5-fluorodeoxyuridine compared to stains that have linear chromosomes.